Nations of the Northwest Coast - Smithyman, Kathryn (Crabtree Pub., 2004)
Explores how the waters, mountains, and forests of the Pacific Northwest have provided food and shelter for groups such as the Tlingit, the Haida, and the Kwakiutl for thousands of years.